Attracted to Fire - Mills, DiAnn (Thorndike, Me. : Center Point Pub., 2011)
"Special Agent Meghan Connors' dream of one day protecting the president of the United States is about to come true. Only one assignment stands in her way. After the vice president's rebellious daughter is threatened, Meghan is assigned to her protective detail on a secluded ranch in West Texas. Unfortunately, working with Special Agent in Charge Ash Zinders may be as tough as controlling her charge. Ash has a reputation for being critical and exacting, and he's also after the same promotion as Meghan. But when the threats escalate and security on the ranch is breached, it becomes clear this isn't the work of a single suspect-it's part of a sophisticated plan that reaches deeper and higher than anyone imagined. And only Ash and Meghan can put the pieces together before it's too late"-- Cover verso.
Keywords: Secret service -- Fiction -- United States; Teenage girls -- Fiction; Children of presidents -- Fiction -- United States; Large type books; Christian fiction; Love stories